A survey study on Arabic WordNet: baring opportunities and future research directions. (25th May 2021) - Albesher, Abdulmohsen S.; Rabie, Osama B.
WordNet (WN) plays an essential role in knowledge management and information retrieval - as it allows for a better understanding of word relationships, which leads to more accurate text processing. The success of WN for the English language encouraged researchers to develop WNs for other languages. One of the most common of such languages is Arabic. However, the current state of affairs of Arabic WN (AWN) has not been properly studied. Thus, this paper presents a survey study on AWN conducted to explore opportunities and possible future research directions. The results involve the synthesis of over 100 research papers on AWN. These research papers were divided into categories and subcategories.